Potensi Manusia Perspektif Al-Qur’an Dan Psikologi Behaviorisme Dan Humanisme Serta Implikasinya Dalam Pendidikan - Jamil Abdul Aziz (Qiro'ah : Jurnal Pendidikan Agama Islam, 2019)
This article explains about how the Qur'an and Psychology as a science that focuses on talking about human behavior and mentality discuss the basic concepts and potential that exists in humans and how it is applied of education. The method used in this research is qualitative with library research method with descriptive analysis approach. From the searches that have been made at least it can be concluded that the Koran sees humans as physical (biological or material) and spiritual (spiritual) beings, whereas Psychology generally only sees humans as mere physical beings